2018
DOI: 10.1177/0020715217753271
|View full text |Cite
|
Sign up to set email alerts
|

Gender and highbrow cultural participation in Europe: The effect of societal gender equality and development

Abstract: Existing individual-level research links women’s higher participation in high-status cultural activities to their position in work and family spheres. This article studies how cross-national variation in women’s and men’s cultural participation relates to societal care- and work-related gender equality and development. Multilevel analyses on Eurobarometer data (2013) indicate that male engagement in the feminine domain of care and societal development stimulates frequent participation in highbrow culture, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 71 publications
(153 reference statements)
0
5
0
Order By: Relevance
“…A substantial body of subsequent research, using a wide range of research methods, has found similar findings in a number of different countries (e.g. Bennett et al, 2009;Lena, 2019), and via cross-national comparisons (Falk & Falk, 2011;Falk et al, 2016;Katz-Gerro, 2017;Lagaert et al, 2018;Reeves, 2019;Van Hek & Kraaykamp, 2013). Extensive, often highly-technical, academic debates have taken place since the first edition of Distinction regarding whether and how Bourdieusian theories can be tested.…”
Section: Understanding the Stratification Of Cultural Consumptionmentioning
confidence: 90%
“…A substantial body of subsequent research, using a wide range of research methods, has found similar findings in a number of different countries (e.g. Bennett et al, 2009;Lena, 2019), and via cross-national comparisons (Falk & Falk, 2011;Falk et al, 2016;Katz-Gerro, 2017;Lagaert et al, 2018;Reeves, 2019;Van Hek & Kraaykamp, 2013). Extensive, often highly-technical, academic debates have taken place since the first edition of Distinction regarding whether and how Bourdieusian theories can be tested.…”
Section: Understanding the Stratification Of Cultural Consumptionmentioning
confidence: 90%
“…This largely echoes the findings of Falk and Katz-Gerro (2016) who showed, in the light of crossnational data, that gender (along with age) has much weaker effects on cultural participation than for instance education. It could also be a possibility that in an egalitarian context such as Finland the decreasing gender gap reflects the suggestion that gender-equal countries would show higher numbers of both men and women participating in culture due to higher rates of more equally shared housework and childcare (Lagaert and Roose, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Eurobarometer surveys are public opinion surveys conducted by the European Commission twice a year since 1973, on a variety of topics. Leong and Ward, 2006;Lagaert and Roose, 2018). In their design, efforts are made to ensure representativeness through criteria such as sex, age or location.…”
Section: Datamentioning
confidence: 99%
“…Nonetheless, Eurobarometer data have been regularly used for scientific publications on a range of topics, including on gender and diversity (e.g. Leong and Ward, 2006;Lagaert and Roose, 2018).…”
Section: Datamentioning
confidence: 99%